Human connection: a valuable element for health-related quality of life outcomes in cardiac rehabilitation during COVID-19. (29th July 2021) - Candelaria, D; Gallagher, R; Ladak, L; Glinatsis, H; Randall, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background The COVID-19 pandemic restrictions have pivoted in-person cardiac rehabilitation (CR) to remote delivery via telehealth. Patient perceptions on their CR participation in these models can guide CR coordinators improve program elements. Purpose To qualitatively explore patient perceptions and experiences on how CR influenced their health-related quality of life (HRQL). Methods A purposive sample of 16 patients were recruited, ensuring representation from four participating CR sites, gender, age, and mode of CR delivery. Semi-structured telephone or video interviews were conducted at six months following CR completion. Interviews were audio-recorded, transcribed verbatim and analysed using Braun and Clarke's six-step thematic analysis. Results Perceptions and experiences of patients were positive overall and similar between the two models. Three main themes were identified: value of human connection, benefits of exercise and need for more individualised approaches, and importance of telehealth as an adjunct to in-person CR. Patients have expressed the value of interacting with health care professionals and socialising with peers in similar circumstances; and the absence of these interactions was palpable to those who attended telehealth. Exercises were beneficial but needed to be tailored to individual capabilities and preferences. Telehealth offered convenience and was generally accepted. However, telehealth should be complementary and not a replacement to in-person CR. Conclusions Meaningful personal interactions with health care providers and other CR participants are most appreciated by patients in both in-person and telehealth models. Exercises are perceived to be more beneficial when individualised. Long-term outcomes from alternative CR delivery models should be evaluated.